Searching for Glycosylated Natural Products in Actinomycetes and Identification of Novel Macrolactams and Angucyclines - Malmierca, Mónica G.; González-Montes, Lorena; Pérez-Victoria, Ignacio; Sialer, Carlos; Braña, Alfredo F.; García Salcedo, Raúl; Martín, Jesús; Reyes, Fernando; Méndez, Carmen; Olano, Carlos; Salas, José A. (Frontiers in Microbiology, 2018)
Many bioactive natural products are glycosylated compounds in which the sugar components usually participate in interaction and molecular recognition of the cellular target. Therefore, the presence of sugar moieties is important, in some cases essential, for bioactivity. Searching for novel glycosylated bioactive compounds is an important aim in the field of the research for natural products from actinomycetes. A great majority of these sugar moieties belong to the 6-deoxyhexoses and share two common biosynthetic steps catalyzed by a NDP-D-glucose synthase (GS) and a NDP-D-glucose-4,6-dehydratase 4,6DH). Based on this fact, seventy one Streptomyces strains isolated from the integument of ants of the Tribe Attini were screened for the presence of biosynthetic gene clusters (BGCs) for glycosylated compounds. Total DNAs were analyzed by PCR amplification using oligoprimers for NDP-D-glucose synthases and NDP-D-glucose-4,6-dehydratases and also for a NDP-D-glucose-2,3-dehydratases. Amplicons were used in gene disruption experiments to generate nonproducing mutants in the corresponding clusters. Eleven mutants were obtained and comparative dereplication analyses between the wild type strains and the corresponding mutants allowed in some cases the identification of the compound coded by the corresponding cluster (lobophorins, vicenistatin, chromomycins and benzanthrins) and that of two novel macrolactams (sipanmycin A and B). Several strains did not show UPLC differential peaks between the wild type strain and mutant profiles. However, after genome sequencing of these strains, the activation of the expression of two clusters was achieved by using nutritional and genetic approaches leading to the identification of compounds of the cervimycins family and two novel members of the warkmycins family. Our work defines a useful strategy for the identification new glycosylated compounds by a combination of genome mining, gene inactivation experiments and the activation of silent biosynthetic clusters in Streptomyces strains.